Chemical composition and antibacterial activity of essential oils of Thymelaea hirsuta from Algeria - Souheila Bounab; Takia Lograda; Messaoud Ramdani; Pierre Chalard; Gilles figueredo (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Souhila B, Takia L, Messaoud R, Pierre C, Gilles F. 2019. Chemical composition and antibacterial activity of essential oils of Thymelaea hirsuta from Algeria. Biodiversitas 20: 2868-2876. The objectives of this study were to determine the chemical composition and to evaluate the antibacterial activity of Thymelaea hirsuta (L.) Endl., essential oils from seven sampling locations in M'sila region (Algeria). Extraction of essential oils was carried out by the hydro-distillation; the analysis of chemical composition of essential oil was carried out by GC-MS. Antimicrobial activity was performed by disc diffusion method at the essential oil concentration of non-diluted and diluted (1:2, 1:4 and 1:8 v:v of DMSO) against eight species of bacteria. The results showed that the average yields of essential oils were 0.3 ± 0.12%. A total of 45 components were identified, averaging 98.2 ± 1.85% of the total oils. The main components were nonanal-n (10.39 ± 3.21%), hexadecanoic acid (9.77 ± 2.81%), nonanoic acid (9.13 ± 6.49%), triacontane (7.2 ± 3.34%), isopropyl tetradecanoate (6.16 ± 1.99%) and tridecane (4.87 ± 3.1%). Based on the UPGMA cluster analysis, there were two clades of T. hirsuta. T. hirusta has a chemical polymorphism with different chemotypes marked in nature. There were four chemotypes identified in the essential oil of T. hirsuta in the region of M'sila. The essential oil of T. hirsuta has antibacterial activity against eight tested bacteria on the concentration-dependentt manner.